Akuisisi Data dan Pengolahan Isyarat Elektrokardiograf Menggunakan Modul USB Dataq DI-148U - Henry Sulistyo; Thomas Sri Widodo; Maesadji Tjokronagoro; Indah Soesanti (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Heart signal data acquisition for the purpose of research is still an obstacle when using the standard ECG equipment from the manufacturer. The problem is the expensive equipment and the conversion of images into digital data. By using instrumentation amplifiers and electronic components in the market can be realized a simple ECG prototype by using interface Dataq DI-148U USB module for cardiac signals data acquisition.In this study, single channel ECG prototype realized with twelve leads by manually selected. Tests using five subjects that compared the results with standard hospital ECG equipment.From ECG prototype tests each sub section, the results are in accordance with the planning. The use of adhesive floating electrode type showed a smaller noise. IIR digital filter effectively reduces noise with SNR above of 20 dB and baseline wander at frequency cutoff 0.95 Hz. The threshold method is capable of detecting the peak R-R interval well to calculate the heart rate.